1.4k views
1 vote
B-2a^2/b^2-a/b^2-a where a=-3 and b=-1 answer should be in a improper fraction, if appropriate.

User Buzuosheng
by
4.7k points

1 Answer

1 vote

Answer:


\Rightarrow -(73)/(4)

Explanation:

The given expression,
(b-2a^2)/(b^2)-(a)/(b^2-a)

where, a = -3 and b = -1

Put the value of a and b into expression


\Rightarrow ((-1)-2(-3)^2)/((-1)^2)-((-3))/((-1)^2-(-3))

Simplify each parentheses


\Rightarrow (-1-18)/(1)+(3)/(1+3)


\Rightarrow -19+(3)/(4)

Now make same denominator


\Rightarrow -(76)/(4)+(3)/(4)


\Rightarrow (-76+3)/(4)


\Rightarrow -(73)/(4)

This is improper fraction because numerator is greater than denominator.

User Kingkong Jnr
by
4.5k points